Factors Affecting The Implementation Of Occupational Safety And Health At Royal Prima Medan General Hospital In 2021 - Frisca Gemmi Deseva; Chrismis Novalinda Ginting; Muhammad Aditya Kurnia (CV. Inara, 2022)
Cases of Occupational Accidents (KAK) and Occupational Diseases (PAK) at Royal Prima Hospital Medan in 2017-2020 showed a significant increase, especially in 2020. This condition was due to Royal Prima Hospital receiving/serving Covid-19 patients so that they were overwhelmed in handling The surge in patients impacting the workforce is experiencing fatigue and illness. The purpose of this study is to analyze the factors that influence the implementation of Occupational Safety and Health (K3). This research is a quantitative analytic study with a cross-sectional approach. The research was conducted at Royal Prima Hospital Medan. The research population was 915 people and the sample was 100 people. Sampling by the Hsystematic way (systematic sampling). Data analysis used univariate, bivariate with chi-square test, and multivariate with multiple logistic regression at 95% confidence level (α=0.05). The results showed that the factors that influenced the implementation of Occupational Safety and Health (K3) at Royal Prima Hospital Medan were action (p=0.045), policy (p=0.010), standard operating procedures (p=0.011), and leadership (p=0.011). = 0.020). Variables that had no effect were education (p=0.461), belief (p=0.538), perception (p=0.235), knowledge (p=0.578) and attitudes (p=0.730). The most dominant variable influencing the implementation of K3 at Royal Prima Hospital Medan is policy. Implementing officers who declare hospital policies are good, have a 5.5 times higher chance of implementing K3 well than those who state policies are not good.